Development and Quality Evaluation of Immune-Boosting Jelly Candy Using Natural Ingredients. - Mohamedsalih Abdallah, Hagir; Attia Amer Abu Awaja, Alaa (Scientific Journal of University of Benghazi, 2025)
This study aimed to develop jelly candy with natural ingredients that have immune-boosting properties. Four candy samples were prepared from ingredients including lemon, beetroot, carrot, orange, pomegranate, strawberry, ginger, turmeric, black pepper, and gelatin. Two samples were sweetened with natural honey, and two with stevia sugar. Traditional gelatin candy from the local market was used for comparison. The samples were subjected to analysis of chemical quality properties, proximate composition, phytochemical analysis, mineral content, microbial analysis, and sensory evaluation. The most important results obtained showed that the prepared samples contained good levels of protein, fiber, and potassium, which were 6.87±0.009%, 3.55±0.003%, and 64±2 ppm, respectively. The beetroot, pomegranate, and strawberry samples had excellent iron content (35±2 and 31±2 ppm) for the honey-sweetened and stevia-sweetened samples, respectively. The preliminary screening results for phytochemical compounds showed that the prepared samples were rich in phenols, glycosides, and tannins (+++), while the samples sweetened with natural honey had excellent saponin content (+++). Microbial analysis revealed that the samples were free of coliform bacteria and E. coli. Sensory evaluation results revealed that the participants preferred the stevia-sweetened samples in all tested attributes, including color, taste, flavor, and overall acceptability, with a (very good) rating. The study recommended the development of a functional food industry based on natural food ingredients rich in macro- and micronutrients and active chemical compounds.